Speed up Eulerian Video Motion Magnification - Hussain, Yossra; Shkara, Ahmed A. (Kurdistan Journal of Applied Research, 2017)
A standard video can have small video motions that are difficult to see by naked eye because of it limited sensitivity. These hidden signals variation may have highly useful information that can be used in variety of applications fields such as healthcare, biology, mechanical engineering, civil engineering, military and security. Eulerian Video Motion Magnification is a system used to detect and amplified tiny motions in video. This system have a problem with processing time, it consumes too long time to complete the spatial _ temporal analyzing. This paper, proposes a modified approach to Speed up the processing time of Eulerian motion magnification, it minimizes the analyzing area of frames and applying the analyzing process only on a tiny motion area and ignores all unchanged background. The test results show that the proposed approach has speed up the processing time of Eulerian Motion Magnification may be to , more than 70% percentage